1982
DOI: 10.1172/jci110720
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation by collagen and 15-hydroxy-9 alpha,11 alpha-peroxidoprosta-5,13-dienoic acid (PGH2) of phosphatidylinositol metabolism and arachidonic acid release in human platelets.

Abstract: A B S T R A CT Collagen stimulates the activation of phosphatidylinositol (PI)-specific phospholipase C (EC 3.1.4.10) in human platelets, as manifested by the disappearance of PI, the transient formation of diacylglycerol (DG), and release of myoinositol. Platelets exposed to collagen also form lysophosphatidylinositol (LPI). Maximum formation of DG occurs within 60 s of the addition of collagen and is in proportion to the concentration of collagen provided, up to 100 Mg!2 X 109 platelets/ml. Hydrolysis of PI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
40
0
2

Year Published

1985
1985
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 28 publications
(22 reference statements)
9
40
0
2
Order By: Relevance
“…Presumably, TXA2 is generated during the action of collagen, increases cytoplasmic free Ca'+, and finally stimulates collagen-initiated phosphoinositide turnover. It is evident from our results as well as earlier observations [4,17] that Ca2+ mobilization alone is not sufficient and the occupation of the receptor with collagen is absolutely necessary for the induction of phosphoinositide turnover.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Presumably, TXA2 is generated during the action of collagen, increases cytoplasmic free Ca'+, and finally stimulates collagen-initiated phosphoinositide turnover. It is evident from our results as well as earlier observations [4,17] that Ca2+ mobilization alone is not sufficient and the occupation of the receptor with collagen is absolutely necessary for the induction of phosphoinositide turnover.…”
Section: Discussionsupporting
confidence: 74%
“…These arachidonic acid metabolites have been shown to induce secretion and aggregation [2,3]. Based on these observations, it has been suggested that PGH2 and TXA2 may play a role of crucial importance in the action of collagen [2- [4] have shown that PGH2 and its stable analogue U46619 induce phosphoinositide turnover to a small extent but counteract the inhibition by aspirin of collagen-induced phosphoinositide turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen-induced Production of TXA Enhances the Increase in [Ca 2ϩ ] i and [Na ϩ ] i -TXA, produced subsequent to platelet activation with collagen (48), enhances collagen-induced activation (6,(13)(14)(15). Inhibiting TXA production with aspirin reduced the collagen-induced increase in [Ca 2ϩ ] i and aggregation and was almost completely abolished by the chelation of extracellular Ca 2ϩ .…”
Section: Collagen-induced Platelet Aggregation a Ca 2ϩ -Dependentmentioning
confidence: 99%
“…At high concentrations, collagen activation of platelets has been shown to proceed through activation of phospholipase C␥2 and subsequent cleavage of phosphatidylinositol 4,5-bisphosphate into inositol 1,4,5-trisphosphate and 1,2-diacylglycerol (6,7). Inositol 1,4,5-trisphosphate induces the release of calcium from the dense tubular system (8,9), whereas 1,2-diacylglycerol activates protein kinase C (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation